2003
DOI: 10.1074/jbc.m212715200
|View full text |Cite
|
Sign up to set email alerts
|

Domains in Tropoelastin That Mediate Elastin Depositionin Vitro and in Vivo

Abstract: Elastic fiber assembly is a complicated process involving multiple different proteins and enzyme activities. However, the specific protein-protein interactions that facilitate elastin polymerization have not been defined. To identify domains in the tropoelastin molecule important for the assembly process, we utilized an in vitro assembly model to map sequences within tropoelastin that facilitate its association with fibrillin-containing microfibrils in the extracellular matrix. Our results show that an essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 44 publications
4
140
0
Order By: Relevance
“…It may be possible that the aggregation into such well defined, nanoordered assemblies represents a state of an efficient minimal energy arrangement of polypeptide chains (15)(16)(17). Recent results have shown that fibrillar structures similar to amyloid fibrils are formed by sequences like poly(XGlyGlyYGly) (X, Y ϭ Val, Leu, or Ala), which are highly repeated in the hydrophobic domains of elastin (18,19).…”
Section: Charge Transport and Intrinsic Fluorescence In Amyloid-like mentioning
confidence: 99%
“…It may be possible that the aggregation into such well defined, nanoordered assemblies represents a state of an efficient minimal energy arrangement of polypeptide chains (15)(16)(17). Recent results have shown that fibrillar structures similar to amyloid fibrils are formed by sequences like poly(XGlyGlyYGly) (X, Y ϭ Val, Leu, or Ala), which are highly repeated in the hydrophobic domains of elastin (18,19).…”
Section: Charge Transport and Intrinsic Fluorescence In Amyloid-like mentioning
confidence: 99%
“…In the alternate succession of hydrophobic and cross-linking domains, peculiar of tropoelastin (27), this peptide belongs to the C-terminal hydrophobic domains of human tropoelastin and has been indicated as fundamental for a correct assembly of elastin (10). It is a glycine-rich domain, containing 13 glycine residues up to 25 residues, and contains only hydrophobic residues.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the disruption of the disulfide bond dramatically reduces the ability of tropoelastin to assemble and be included in developing fibers, as it does the removal of the C-terminal region. 16 Therefore, we can speculate that the mutant tropoelastin, if secreted from the cell, would likely impair the tropoelastin from assembling in a dominant-negative manner, resulting in a deleterious effect on the normal elastogenesis in those patients. A definitive resolution of this issue would require arterial smooth muscle in order to investigate whether these mutations yield abnormal elastin and/or normal elastogenesis, but this kind of tissue is not available.…”
Section: Discussionmentioning
confidence: 99%